ANALISIS EFEKTIVITAS SISTEM RECEIVING DAN STOREKEEPING DALAM MENDUKUNG PENGENDALIAN INTERNAL PERSEDIAAN PADA HOTEL MERCURE - Boby Gunarso; Fatkhul Sani Rohana (Adisam Publisher, 2026)
This study aims to analyze the effectiveness of receiving and storekeeping systems in supporting internal inventory control at Mercure Hotel. The method used is a descriptive qualitative approach with data collection techniques through observation and documentation. The results show that both systems have been operating very effectively, with an effectiveness level above 90%. The receiving system demonstrates good performance through the conformity of goods with purchase orders, completeness of documents, and high recording accuracy. The verification process carried out carefully is able to minimize errors and potential fraud from the initial stage of receiving goods.Meanwhile, the storekeeping system also shows high effectiveness, indicated by stock accuracy and minimal discrepancies between system data and physical conditions. The implementation of the FIFO method, proper warehouse layout management, and strict supervision are the main supporting factors. The integration between receiving and storekeeping systems creates a systematic, transparent, and accountable inventory management flow. In addition, information technology support further enhances efficiency and data reliability. Overall, these two systems contribute significantly to operational efficiency and internal inventory control of the hotel.